The Effect of The Combination Of Carde Waste, Dry Banana Leaves (Klaras) and Rice Husb As A Planting Media for Growth of Straw Mushroom (Volvarieela Volvacea L) - Nabila Rizka Anisa; Samingan Samingan; Hafnati Rahmatan; Iswadi Iswadi; Wiwit Artika (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2021)
ABSTRACTMushroom cultivation has bright prospects because the natural and environmental conditions in Indonesia are very supportive. Straw is a planting medium that is commonly used for the growth of edible mushrooms. Cardboard, klaras and husks are one of the household wastes that can be used as an alternative planting medium for mushroom as a substitute for straw. This study seeks to find out the effect of a combination of cardboard. Klaras and rice husks as a growing medium for mushroom and to find out the comparison of the composition of cardboard waste and klaras growing media that can have the best effect on the growth of edible mushrooms. This research was conducted in Rukoh Village, Banda Aceh from October to November 2019 for ± months. This study used a quantitative method in the form of an experiment with a completely randomized design (CRD) consisting of 7 treatments and 4 replications. Data were analyzed using further test of Least Significant Difference (LSD). The results showed that cardboard waste, klaras and husks had the best effect on the growth of edible mushrooms on the wet weight of mushroom and the number of fruit bodies was in treatment 6 with the composition (cardboard 25% + Straw 25% + and husks 50%) with average weight. Wet 25.97 grams and the average number of fruit bodies 4.53. Whereas the effect of cardboard waste, klaras and husks has an effect on the growth of mushroom with the best growth in the size of mushroom fruit body diameter in treatmen 4 with a combination of 50% cardboard waste, 25% klaras and 25% rice husks with an average body diameter. Mushroom fruit is 6.57 cm.Keywords: Mushrooms, Waste, Cardboard, Klaras, Rice Husk, Planting Media ABSTRAKBudidaya jamur memiliki prospek yang cerah karena kondisi alam dan lingkungan di Indonesia sangat mendukung. Jerami merupakan media tanam yang umum digunakan untuk pertumbuhan jamur merang. Kardus, kelaras dan sekam merupakan salah satu limbah rumah tangga yang dapat dijadikan sebagai alternatif media tanam jamur merang sebagai pengganti jerami. Penelitian ini berupaya mencari tahu pengaruh kombinasi kardus, kelaras dan sekam padi sebagai media tanam jamur merang serta mengetahui perbandingan kombinasi komposisi media tanam limbah kardus dan kelaras yang dapat memberikan pengaruh terbaik pada pertumbuhan jamur merang. Penelitian ini dilaksanakan di Desa Rukoh, Banda Aceh pada Bulan Oktober sampai November 2019 selama ± 2 bulan. Penelitian ini menggunakan metode kuantitatif dalam bentuk eksperimen dengan Rancangan Acak Lengkap (RAL) terdiri dari 7 perlakuan dan 4 ulangan. Data dianalisis menggunakan uji lanjut Beda Nyata Terkecil (BNT). Hasil penelitian menunjukkan limbah kardus, kelaras dan sekam berpengaruh terhadap pertumbuhan jamur merang yang paling baik terhadap berat basah jamur merang serta jumlah tubuh buah adalah pada perlakuan 6 dengan komposisi (kardus 25% + jerami 25% dan sekam 50%) dengan rata-rata berat basah 25,97 gram dan rata-rata jumlah tubuh buah 4,53. Sedangkan pengaruh limbah kardus, kelaras dan sekam berpengaruh terhadap pertumbuhan jamur merang yang paling baik pertumbuhan ukuran diameter tubuh buah jamur merang yang paling baik pada perlakuan 4dengan kombinasi 50% limbah kardus, 25% kelaras dan 25% sekam padi dengan rata-rata diameter tubuh buah jamur merang adalah 6,57 cm.Kata Kunci: Jamur Merang, Limbah, Kardus, Kelaras, Sekam Padi, Media Tanam